Pengaruh Fasilitas dan Promosi Terhadap Keputusan Berkunjung Destinasi MICE di Wisata Srp Ernala Sukanalu Simbelang - Lirbryna Evani Br Tarigan; Jamardua Haro (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Srp Ernala Tourism is one of the tourist destinations located in Sukanalu Simbelang village, Karo Regency, North Sumatra. Srp Ernala Tourism Destination not only displays the beauty of the Karo Regency region but displays Karo Regency culture, cleanliness of the place, friendliness of service and provides many facilities to provide tourist comfort when visiting Srp Ernala Tourism. other than facilities, promotion is one of the success factors of a marketing program with promotions that can increase tourist visits. This study aims to determine the effect of facilities and promotions on visiting decisions for MICE Destinations at Srp Ernala Sukanalu Simbelang Tourism. The research was conducted at Srp Ernala Sukanalu Simbelang Tourism which is located in Sukanalu Simbelang Village, Barusjahe District, Karo Regency, North Sumatra in 2023. This research uses quantitative research methods. The population in this study amounted to 100 visitors. Data collection was carried out using questionnaires and observations at tourist sites. Data processing techniques include validity test, reliability test, classical assumption test, hypothesis testing (t test, f test, and coefficient of determination analysis test (R2). The results of this study indicate that facilities, promotion positively and significantly influence the decision to visit the MICE Destination Srp Ernala Sukanalu Simbelang Tourism. Promotion has the most dominant influence on visitor decisions.